Analisis Finansial Alat Tangkap Pancing Ulur di Desa Inobonto Kecamatan Bolaang Kabupaten Bolaang Mongondow - Mokoagow, Nelawati; Manoppo, Victoria E.N.; Pangemanan, Jeannette F.; Durand, Swenekhe S.; Tambani, Grace O.; Aling, Djuwita R.R. (Universitas Sam Ratulangi, 2024)
Abstract The purpose of this study was to describe the profile of fishermen and determine the feasibility of the business through financial analysis of the handline fishing business in Inobonto Village, Bolaang District, Bolaang Mongondow Regency. The basic method used in this study was a survey. The data collected consisted of primary data and secondary data. The data obtained were analyzed using financial analysis formulas and interpreted with quantitative and qualitative descriptive analysis. The results of the study showed that the profile of the handline fishing business was as follows: the average age of fishermen was 46-70 years, had an average education (elementary school), had semi-permanent and permanent houses with an average number of dependents of 3-4 people. The financial feasibility of the handline fishing business had an operating profit of IDR 30,560,000, a net profit of IDR 28,705,000, a profit rate of 148.7%, a Benefit Cost Ratio of 2.48, a BEP of sales of IDR 2,944,444, a BEP of 147 kg. Keywords: handline fishing; fishermen's profile; financial; financial feasibility Abstrak Tujuan penelitian ini ialah mendeskripsikan profil nelayan dan menentukan kelayakan usaha melalui analisis finansial usaha pancing ulur di Desa Inobonto Kecamatan Bolaang Kabupaten Bolaang Mongondow. Metode dasar yang digunakan dalam penelitian ini yaitu survei. Data yang dikumpulkan terdiri dari data primer dan data sekunder. Data yang diperoleh di analisis dengan memakai rumus analisis finansial dan diinterprestasikan dengan analisis deskriptif kuantitatif dan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa profil usaha nelayan pancing ulur sebagai berikut: umur nelayan rata-rata 46-70 tahun, memiliki pendidikan rata-rata (SD), memiliki rumah semi permanen dan permanen dengan jumlah tanggungan rata-rata 3-4 orang. Kelayakan finansial usaha pancing ulur memiliki operating profit Rp30.560.000, net profit Rp28.705.000, profit rate 148,7%, Benefit Cost Ratio 2,48, BEP penjualan Rp 2.944.444, BEP satuan 147 kg. Kata kunci: pancing ulur; profil nelayan; finansial; kelayakan finansial